Effects on density, shrinking, color changing and chemical surface analysis through FTIR of Tectona grandis thermo-treated: Density, shrinking, color changing and chemical analysis by FTIR of the thermally-treated teak wood - Moya-Roque, Róger; Méndez-Mejías, Luis Diego (Forest Sciences, 2016)
Thermal-treatment wood is used as an option to improve durability of wood in recent years. This study evaluated the effect of temperature in thermally treated Tectona grandis wood in density, shrinking, color changing (L*a*b* system) and surface analysis through FTIR. Sapwood and heartwood boards sawn with radial and tangential patterns were exposed to three temperature-levels: 210 ºC, 215 ºC, 220 °C during 6 hours and thermally treated wood properties were compared with untreated wood. Results showed that density decreased from 0.61 to 0.49 g cm-3 with a tendency to decrease as temperature increases. Wood shrinking ranges from 2.61 to 1.58 % and no statistical differences between temperatures were found. The FTIR analysis showed a slight increase in the bands at 1024 cm-1, 1098 cm-1, 1131 cm-1, 1249 cm-1 2928 cm-1 and 3340 cm-1 with the temperature increases, indicating a lignin change. Color change showed major changes in luminosity (L*), followed by redness (a*); while yellowness (b*) showed minor changes. Finally, the thermal treatment at 220 °C had the best results regarding the evaluated properties.
Artículo científico
Keywords: Tratamiento térmico; Temperatura; Polímeros; Madera; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING